Antibacterial Activity of Various Solvent Extracts of Some Selected Medicinal Plants Present in Jaffna Peninsula - Jeyaseelan, E. C (International Journal of Pharmaceutical & Biological Archive, 2012)
Antibacterial Activity of Various Solvent Extracts of Some Selected Medicinal Plants Present in Jaffna Peninsula